Network Design and Route Analysis Using Outside Plant - Isaac Adjaye Aboagye; Nii Longdon Sowah; Wiafe Owusu-Banahene; Aryee Shaelijah; Margaret Ansah Richardson; Emmanuel Baah-Boadi (Journal of Engineering)
Outside plant (OSP) is essential for telecommunications, internet, and other communication services that require connectivity beyond indoor spaces. These networks often involve the installation of cables, conduits, cabinets, poles, and other infrastructure elements to connect various locations. However, different service channels such as water pipelines, network cables, and electric cables make the implementation of these installations very challenging. This research presents an investigation into the route design and analysis of fiber architectures, taking into account aerial and underground installations. In this research, a novel safe route that will enable safe, undeterred, and cost-effective OSP fiber optic installation was implemented. A high-level design was produced to realize the optimum structural design and implementation of the backend framework of the fiber system. This method helped to tidy the utility corridors and tackle the problem associated with improper planning and design of passive OSP routes. The area to be worked on was demarcated and specification of the boundaries under consideration was noted. A key position for setting up the fiber distribution terminals (FDTs) was determined after which the area being considered is divided into sections, with each distribution line from the FDT serving one section. This was followed by a low-level design which was more detailed. In this stage, the area under consideration was divided into sections with which different distribution lines to serve each section. This was achieved through the identification of residential clusters. To demonstrate our methodology, we provided fiber to the home (FTTP) to an apartment located in the capital city of Ghana. Estimation of parameters, gathering of information, implementation, testing, and analyses were made, followed by adjustments where necessary. Losses from distances of 0.15–5 km were observed. Individual components in the OSP architecture contributed to fixed losses of 0.7, 10.5, and 10.6 in the optical line terminal (OLT), FDT, and fiber access terminal (FAT), respectively. Actual losses from cable length and the nature of the route ranged from 1.04 to 2.24 dB. A slope of 0.24 dB/km was obtained and this is within the required route loss of less than 1 dB/km in fiber optic transmissions. From the research, it was observed that there was a loss in signal power as distance increased. Also, signal loss at a wavelength of 1550 nm was better than signal loss at 1310 nm. Our research revealed a balanced loss of 0.35 dB/km for 1310 nm wavelengths and 0.25 dB/km for 1550 nm. The total distribution length loss for core cables 1, 2, 3, and 4 at wavelengths of 1310 nm were 1.0307, 0.76556, 1.1719 dB, and 1.1322 dB, respectively. The total distribution length loss for core cables 1, 2, 3, and 4 at wavelengths of 1550 nm were 0.7362, 0.5468, 0.837, and 0.8087 dB, respectively. FAT Power (dBm) for feeder lines 1, 2, 3, and 4 and distribution lines 1, 2, 3, and 4, respectively, were all within the acceptable range. The design will help to reduce the cost of repairing damaged cables drastically. Also, the design methodology helped us to develop a backbone network to get closer to the various homes and premises. The architecture was also designed to prioritize the bandwidth demand by clients at the premises. The significance and impact of the research are essential in enhancing efficiency, reducing costs, improving reliability, and ensuring scalability in network design and route analysis. The integration of novel technologies and innovative methodologies makes them relevant in today’s fast-evolving technologies.